THE EFFECT OF SPEAKING SELF-EFFICACY AND GENDER IN SPEAKING ACTIVITIES - Sundari, Hanna; Dasmo, Dasmo (Universitas Pendidikan Indonesia, 2014)
The present study tries to find out the effect of speaking self-efficacy and gender in speaking activities particularly in English as second/foreign language situation, using questionnaire from Banduraâ€™s Guide for constructing self-efficacy scales. The Samples of this study were 23 male and 27 female college-students from speaking classes.Â ANOVA and T-test helped by SPSS 15.0 for windows were employed to investigate speaking self-efficacy, gender and speaking activities. The result showed that the level of speaking self-efficacy both male and female students is moderate. They can moderately perform speaking activities but they think them quite though and difficult. Besides, Sig. for gender scores lower than .05 (.013 .05), gender gave significant effect towards speaking activities. Yet, not only speaking self-efficacy partially (Sig .162 .05) but also its simultaneous interaction with gender (Sig .0677 .05) did not affect significantly towards speaking activities.